Men, gender divisions, and welfare - Popay, Jennie; Hearn, Jeff, 1947-; Edwards, Jeanette, 1954- (Routledge, 1998)
A fresh look at the balance of responsibilities and control in care-giving, in both the public and private spheres. Using previously unpublished empirical data, contributors focus on male experiences of welfare services.